2020
DOI: 10.5539/ijbm.v15n9p75
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Responsible Leadership (RL) on Responsible Employee (RE): The Mediating Role of Sustainable Leadership (SL)

Abstract: Business leaders are facing an uncertain issue regarding what extent their actions and decisions are responsible for the sustainable development supported by Responsible Employees. Although, several papers are discussing the concept of Responsible Leadership (RL) and Sustainable Leadership (SL). However, there is still an important missing element connected to these two leadership approaches which are Responsible Employee/s (RE). The purpose of this paper is to explore how Responsible Leadership and Sustainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Maak and Pless (2009, p. 539) noted that RL is “a value-based and principle-driven relationship between leaders and stakeholders who are connected through a shared sense of meaning and purpose through which they raise to higher levels of motivation and commitment for achieving sustainable value creation and responsible change”. Several value-based leadership approaches have been applied to examinations of employee performance outcomes (Yahaya and Ebrahim, 2016; Shaaban, 2020). For example, both ethical and transformational leadership have demonstrated significant positive relationships with organisational commitment and employee turnover intentions (Gill et al , 2011; Haque et al , 2019c).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Maak and Pless (2009, p. 539) noted that RL is “a value-based and principle-driven relationship between leaders and stakeholders who are connected through a shared sense of meaning and purpose through which they raise to higher levels of motivation and commitment for achieving sustainable value creation and responsible change”. Several value-based leadership approaches have been applied to examinations of employee performance outcomes (Yahaya and Ebrahim, 2016; Shaaban, 2020). For example, both ethical and transformational leadership have demonstrated significant positive relationships with organisational commitment and employee turnover intentions (Gill et al , 2011; Haque et al , 2019c).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…At present, the concept of RL is generating a significant amount of attention among scholars and practitioners because it influences organisational phenomena such as employee commitment, employee performance, turnover intentions and organisational effectiveness (Miska and Mendenhall, 2018; Haque et al , 2019c, 2020). Although RL has been shown to have the potential to enhance organisational performance (Voegtlin et al , 2012; Miska et al , 2013; Shaaban, 2020), there is limited practical evidence showing the influence of RL on employee outcomes (Haque et al , 2019c, 2020). Moreover, while there is evidence of a link between leadership and presenteeism, little is known of the relationship between RL, organisational commitment and employees' turnover intentions.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…This explanation related to RL attempts to merge economic, environmental, and social responsibilities as part of the strategic view. A clear essential commonality, important in the three levels, is the assumption that managers have the freedom of decision in their work roles (Carrol, 2015;Shaaban, 2020). Pless, Maak, and Waldman (2012) have developed a model of RL which outlines four main approaches to the RL phenomenon based on the scope of constituent groups which considered what managers must focus on in their organizations, as well as the accountability of managers toward other shareholders and the owners of businesses.…”
Section: An Analysis Of Previous Theorymentioning
confidence: 99%
“…Variables included are followers' evaluation, followers' perspective, and 360 degrees toward RL. Shaaban (2020) shows that responsible leadership sets the environmental base for the responsible employee; she also demonstrated that to have a responsible employee, we should have responsible leadership, and both, in turn, will lead to sustainability (Shaaban 2020). At the level of followers, when leaders apply the RL approach in their organisation, the leaders in our sample organisations communicate with followers and set the system to translate the concept of responsibility.…”
Section: The Dimension Of the Followers' Perspectivementioning
confidence: 99%
See 1 more Smart Citation